Polysaccharides of Aspergillus cristatus attenuate obesity by regulating gut microbiota and gut microbiota-related metabolites - Mingzhi Zhu; Bohao Shang; Fang Zhou; Yong Yuan; Feiyan Yin; Jin Cao; Jianan Huang; Kunbo Wang; Xin Zeng; Maiquan Li; Zhonghua Liu (Food Science and Human Wellness)
Golden-flower fungus, the only dominant microorganism determining the Fu-brick tea quality through fermentation and the important microbe in Liupao tea, is considered a potential probiotic fungus based on its anti-obesity effect. However, the classif ication of golden-f lower fungi is still controversial; the anti-obesity effect of golden-f lower fungus polysaccharides remains unknown. In this study, we identify a golden-f lower strain as Aspergillus cristatus based on morphological characteristics and multigene phylogeny analysis, which resolves the controversy of classif ication. Moreover, we f ind A. cristatus polysaccharides (ACPS) attenuate obesity in rats. ACPS modulate gut bacterial composition, in which Akkermansia, Akkermansia muciniphila, Bacteroides, Romboutsia, Blautia, and Desulfovibrio are considered the core microbes regulated by ACPS.ACPS increase fecal total short-chain fatty acid content and serum, hepatic, and fecal total bile acid content. Furthermore, ACPS-induced gut microbiota alteration plays a causal role in the protection from obesity, according to a fecal transplantation experiment. Thus, ACPS ameliorate obesity by regulating gut microbiota and gut microbiota-related metabolites.